Analysis of the Development of Food Crops in Supporting Sustainable Agriculture in West Pasaman Regency - Sukarli Sukarli; Rahmat Syahni; Elfindri Elfindri; Hery Bachrizal Tanjung (Eduvest - Journal of Universal Studies, 2025)
The food crop subsector plays a crucial role in regional development by contributing to food security, farmer welfare, and rural economic stability. West Pasaman Regency, one of the main food production centers in West Sumatra, has significant potential but faces challenges such as productivity fluctuations, land conversion, and socio-economic issues among farmer households. This research, titled Analysis of the Development of Food Crops in Supporting Sustainable Agriculture in West Pasaman Regency, aims to identify the economic, social, and environmental conditions of the subsector and formulate holistic recommendations for supporting sustainable agriculture. The study employs secondary data analyzed descriptively, quantitatively, and qualitatively, using trend analysis and Shift Share to evaluate competitiveness. Results indicate that the food crop subsector in West Pasaman is projected to grow by 1.67% in 2024, higher than the provincial rate of 0.57%. The positive Competitive Effect suggests a local competitive advantage. However, unstable rice GDP and productivity, an increasing poor population, and ongoing land conversion remain threats to sustainability. Based on the analysis, strategic recommendations focus on three pillars: (1) economic—boosting productivity through eco-friendly technology, diversification, and downstream processing; (2) social—strengthening farmer institutions, regenerating agricultural labor, and ensuring food-based social protection; and (3) environmental—protecting productive land, conserving resources, and promoting sustainable cultivation practices. Overall, the development of the food crop subsector must adopt a holistic approach to enhance regional competitiveness and achieve sustainable development goals.